Pengaruh Disiplin Kerja terhadap Kualitas Pelayanan Badan Penanggulangan Bencana Daerah Kabupaten Tambrauw - Paa, Luther; Longkutoy, Meyta; Timisela, Yanti M. (CV. Creative Tugu Pena, 2022)
This study aims to analyze the effect of work discipline on employee performance at the Regional Disaster Management Agency of Tambrauw Regency, West Papua Province. The data analysis method used is quantitative descriptive analysis. significant test through (t-test), using simple linear regression and coefficient of determination (R2). The population in this study were all employees of the Regional Disaster Management Agency of Tambrauw Regency, West Papua Province. All of the population involved in the sample amounted to 54 respondents. Primary data were obtained through interviews, questionnaires and documentation studies. From the results of data processing with simple linear regression analysis, the regression equation was obtained. Y = 1.115 + 0.895X, the regression coefficient value of 0.895 means that every time there is a change and addition of one percent to the work discipline variable, the employee performance variable will increase by 0.895 if the work discipline variable is zero, then employee performance has a value of 1.115. In the coefficient of determination test obtained R square 54.4.%, meaning that work discipline affects the quality of service by 54.4%, while the remaining 45.6% is influenced by other factors not analyzed in this study. The results of the t test, where tcount 7.169 > ttable , it can be said that the work discipline variable has a positive and significant effect on employee performance Keywords: Service Quality, Management Agency, Work Dicipline